Tinjauan Aspek Keamanan dan Kerahasiaan Rekam Medis di Rumah Sakit Setia Mitra Jakarta Selatan - Siswati Siswati; Dea Ayu Dindasari (Poltekkes Kemenkes Semarang, 2019)
Maintaining the confidentiality of the patient's medical record, required storage of medical records that meet the requirements in maintaining security and confidentiality. Medical record storage can be said to be good if the room guarantees security and avoid the threat of loss, neglect, disaster and anything that can jeopardize the medical record. The medical record storage room at Setia Mitra Hospital is not yet secure, because the door is unlocked. Besides nurses, radiology and nutrition can enter the medical record storage room and some medical records were found damaged. The general purpose of this study was to determine the security and confidentiality aspects in the medical record storage room. This research method is qualitative with a case study approach to illustrate how the security and confidentiality aspects in the Setia Mitra Hospital medical record storage room. Data collection techniques by observation and interview. The results found that the security and confidentiality policies have been made but have not been implemented well. The conclusion from the results of this study was only found about security policies while standard operating procedures related to the security and confidentiality of medical records have not been made. The physical medical record does not guarantee the safety and confidentiality of the contents of the medical record. Medical record storage room does not guarantee the security of medical record storage. The Setia Mitra Hospital leadership should be able to reaffirm the established policies related to the security and confidentiality of medical records, in addition to that the SPO was made related to the security and confidentiality of medical records.